2006
DOI: 10.1200/jco.2006.06.3958
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Predictors of Outcome With Gefitinib in a Phase III Placebo-Controlled Study in Advanced Non–Small-Cell Lung Cancer

Abstract: EGFR gene copy number was a predictor of clinical benefit from gefitinib in ISEL. Additional studies are warranted to assess these biomarkers fully for the identification of patients most likely to benefit from gefitinib treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
463
8
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 660 publications
(496 citation statements)
references
References 30 publications
19
463
8
6
Order By: Relevance
“…These findings suggest that, based on current paradigms of assessing responsiveness to EGFRtargeted therapies in carcinomas, it is uncertain whether epithelioid sarcomas would show a meaningful response to EGFR tyrosine kinase inhibitors. Nevertheless, one study in refractory, advanced nonsmall cell lung carcinoma has shown EGFR protein expression as a biomarker predictive of better survival, 33 suggesting that EGFR expression may have at least some clinical implication in sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that, based on current paradigms of assessing responsiveness to EGFRtargeted therapies in carcinomas, it is uncertain whether epithelioid sarcomas would show a meaningful response to EGFR tyrosine kinase inhibitors. Nevertheless, one study in refractory, advanced nonsmall cell lung carcinoma has shown EGFR protein expression as a biomarker predictive of better survival, 33 suggesting that EGFR expression may have at least some clinical implication in sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of biomarkers and clinical response in this trial identified high EGFR gene copy number as a predictor of clinical benefit with gefitinib (Hirsch et al, 2006). High EGFR gene copy numbers were detected in 31% of 370 patients with tissue samples available for FISH analysis, and a high EGFR protein expression was found in 70% of 379 evaluable patients.…”
Section: Predictive Value Of Egfr Amplification and Overexpressionmentioning
confidence: 91%
“…The ISEL trial was a double-blind, randomized, placebo-controlled, multicenter phase III study evaluating the efficacy of gefitinib in 1692 patients with refractory, locally advanced or metastatic NSCLC (Hirsch et al, 2006). An analysis of biomarkers and clinical response in this trial identified high EGFR gene copy number as a predictor of clinical benefit with gefitinib (Hirsch et al, 2006).…”
Section: Predictive Value Of Egfr Amplification and Overexpressionmentioning
confidence: 99%
“…Pao et al (2005b) first suggested that patients with NSCLC whose tumors harbor mutations are resistant to EGFR TKI. To date, among 75 NSCLC patients harboring KRAS mutations who were treated with TKIs (Pao et al, 2005b;Hirsch et al, 2006;Massarelli et al, 2007;Miller et al, 2008;Zhu et al, 2008), only one patient has been reported to respond (Zhu et al, 2008). Interestingly, this patient's tumor also had an EGFR gene amplification.…”
Section: Genetic Polymorphisms and Egfr-targeted Drugsmentioning
confidence: 95%
“…In the Italian Expanded Access Study of gefitinib, the BR.21 and the ISEL studies, an association was observed between EGFR FISH positivity and either increased response rates or an improved survival benefit (Hirsch et al, 2003(Hirsch et al, , 2006Tsao et al, 2005;see Hirsch et al, 2009). The high EGFR gene copy number detected by FISH may also be predictive of benefit from chemotherapy combined with cetuximab (Hirsch et al, 2008b).…”
Section: Egfr Fish As a Prognostic And Predictive Biomarkermentioning
confidence: 99%